Relationship Between Maternal Child Handbook Possession and Knowledge Level of Pregnant Mothers Towards its Contents - Tanoto, Nicholas; Ivone Viane Rimbing; Stefani Amelya (Fakultas Kedokteran Universitas Andalas, 2025)
Introduction: Maternal Child Handbook (MCH) is a guidebook belongs to mother and child, which includes information and records on health of mother and her child. However, not every mother in Indonesia owns and utilizes the MCH. While the ownership of MCH does not guarantee that expectant mothers know or understand the contents of MCH, the right utilization of MCH helps in detecting pregnancy related complication as early as possible and would increase intervention acceptance by expectant mothers. Methods: This analytic observational study assessed the knowledge of 38 expectant mothers as respondents towards the contents of MCH. The level of knowledge would then be compared according to the possession of MCH using layered cross-tab analysis in 90% CI. Results: There is a significant difference in total score mean between those who possess MCH and do not possess MCH. Pregnant mothers who own MCH scored 1.63 (90%CI 0.647 – 2.615) points higher than their counterparts. The group of respondents in 1st gravidity shows relationship between MCH possessions towards knowledge score category. Conclusion: There is a relationship between possession of MCH and expectant mothers’ knowledge score towards MCH contents in first pregnancy mothers.